PELATIHAN PEMANFATAAN SAMPAH ORGANIK MENJADI ECO-ENZYME DI KELURAHAN CURUG MANIS - Destri Astrianingsih; Vivit Nurhikmah Havita; Umalihayati Umalihayati; Raden Akhmad Atqoo; Arfian Suryasuciramdhan; Aditya Rachman; Indra Septian; Norma Sri Hastuti; Nazwa Aulia Shihab; Melani Zyahrotul Nadifah; Hiroshi Agung Saputra; Hapid Saepudin; Damar Wulan; Muhammad agung rizki; Shifa Aulia Putri (Amal Insani Foundation, 2023)
The lack of public understanding and awareness regarding the use of organic waste means that there is no organized waste management in the Curug Village environment. So, the aim of this service is to provide knowledge and skills for the community in utilizing organic waste into eco-enzymes as a form of effort to reduce environmental pollution as a result of disorganized waste management. This service method uses a participatory approach by involving housewives in Curug Manis Village, Curug District, Serang City. This service activity began with initial observations related to the discovery of several problems which were then followed up in the form of training activities on the use of organic waste into eco-enzymes.